The Relationship Between Institutional Environment, Guardian Involvement, Academic Achievement and Learning Motivation of Children Reared In a Malaysian Orphanage - Alfred, A.J.; Ma’rof, A.M.; Buang, N. (Jurnal VARIDIKA, 2017)
This research was conducted to study the relationships between academic performance, learning motivation, institutionalised environments and guardian involvement of children reared in a Malaysian orphanage. This study involves 50 students consisting of 21 female and 29 male students. These students are in secondary school with ages ranging from 13-17 years old. This study was conducted in a home for orphans and under-privileged children and all the participants of this study are from this home. The findings of this study show that there is a significant relationship between academic performance, intrinsic motivation, extrinsic motivation and therefore learning motivation as a whole (P<0.05). Findings also show that there is strong correlation between guardian involvement and academic performance (P<0.05). However for relationships between guardian involvement and learning motivation, institutionalised environment and academic performance and institutionalised environment and guardian involvement, correlations fail to exist (P>0.05).